2019
DOI: 10.1111/ruso.12307
|View full text |Cite
|
Sign up to set email alerts
|

The Opioid Hydra: Understanding Overdose Mortality Epidemics and Syndemics Across the Rural‐Urban Continuum

Abstract: The rapid increase of fatal opioid overdoses over the past two decades is a major U.S. public health problem, especially in non‐metropolitan communities. The crisis has transitioned from pharmaceuticals to illicit synthetic opioids and street mixtures, especially in urban areas. Using latent profile analysis, we classify n = 3,079 counties into distinct classes using CDC fatal overdose rates for specific opioids in 2002–2004, 2008–2012, and 2014–2016. We identify three distinct epidemics (prescription opioids,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
75
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(89 citation statements)
references
References 55 publications
5
75
0
3
Order By: Relevance
“…The income inequality-health literature and the aforementioned studies by Monnat (2018Monnat ( , 2019 and Peters et al (2019) also highlight that different parts of the income distribution may affect drugrelated mortality more so than others. The inequalityhealth literature has generally focused on inequality measures that quantify the concentration of income at the top of the distribution or the Gini coefficient that takes into account the entire distribution while giving less attention to the bottom of the income distribution (Hill and Jorgenson 2018;Pickett and Wilkinson 2015;Wilkinson and Pickett 2010).…”
Section: Divergent Perspectives On the Drivers Of The Drug Overdose Ementioning
confidence: 99%
See 1 more Smart Citation
“…The income inequality-health literature and the aforementioned studies by Monnat (2018Monnat ( , 2019 and Peters et al (2019) also highlight that different parts of the income distribution may affect drugrelated mortality more so than others. The inequalityhealth literature has generally focused on inequality measures that quantify the concentration of income at the top of the distribution or the Gini coefficient that takes into account the entire distribution while giving less attention to the bottom of the income distribution (Hill and Jorgenson 2018;Pickett and Wilkinson 2015;Wilkinson and Pickett 2010).…”
Section: Divergent Perspectives On the Drivers Of The Drug Overdose Ementioning
confidence: 99%
“…Monnat (2019), although not explicitly investigating inequality, found that more economically distressed counties have higher drug-related mortality rates. Peters et al (2019), whom also did not investigate inequality explicitly, found that places hit hardest by the prescription-opioid epidemic are those that have been economically left behind. These studies illustrate that economic distress plays a significant role in the drug epidemic and that supply-side factors also matter, but they only tangentially linked their findings to the unequal distribution of resources and power in society.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, there has been a shift in several western countries towards an increasing number of opioid deaths Fig. 2 Opioid-related deaths in Skåne grouped by the substances that caused the intoxication, by period in less densely populated communities outside metropolitan areas [48][49][50]. In this study, the three larger municipalities in Skåne were the places in which access to OST had increased the most and no increase in the proportion of deaths was noted in these.…”
Section: Discussionmentioning
confidence: 83%
“…A previous evaluation has shown proximity to the clinic to be important for patients in OST when choosing a treatment facility [19]. In recent years, there has been a shift in several western countries towards an increasing number of opioid deaths in less densely populated communities outside metropolitan areas [47,48,49]. In this study, the three larger municipalities in Skåne were the places in which access to OST had increased the most and no increase in the proportion of deaths was noted in these.…”
Section: Discussionmentioning
confidence: 99%